Assessing Paragraph Writing Quality of Students' Dissertation Abstract - Sakkir, Geminastiti; Dollah, Syarifuddin; Sakkir, Rini Isnaeni (Yayasan Ahmar Cendekia Indonesia, 2025)
This study investigates the quality of paragraph writing in dissertation abstracts composed by doctoral students in the English Education Study Program at Universitas Negeri Makassar. Motivated by recurring challenges in abstract writing, particularly in terms of coherence, cohesion, and academic language use, this research aims to identify strengths and weaknesses within student abstracts and evaluate the presence of essential abstract components. Employing a qualitative descriptive design, the study analyzed nine abstracts written over the past five years using document analysis and the interactive model of Miles and Huberman. The findings reveal that while most abstracts include key components—such as background, objectives, methods, and results—they often lack explicit concluding statements. Strengths identified include clear topic sentences, formal academic tone, and logical organization. However, issues such as limited use of cohesive devices, partial coherence, redundancy, and verbosity were prevalent in several abstracts. These shortcomings hinder the overall clarity and impact of the writing. The study highlights the importance of structured academic writing training, particularly utilizing cohesion strategies and effective summarization. The results offer valuable insights for enhancing doctoral-level academic writing instruction and can serve as a foundation for further research into writing pedagogy in English as a second language contexts.